ISI Denpasar Fine Arts Study Program MBKM 2023 Artwork Exhibition Display at Living World Denpasar - Ivana, Jessica; Mustika, I Ketut; Utami, Ni Made Purnami (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
Display is a system of arranging objects in a room which aims to display or show off these items. Display in the exhibition space is an important element that needs to be implemented to create an exhibition space that is comfortable for viewing works of art. This becomes a challenge for the exhibiton designer/gallerist to design the best possible exhibition space. The design of the artwork display will affect the visuals and atmosphere of the displayed artwork. In designing exhibition space displays, various concepts, approaches to methods of presenting works can be used. It is this variation of display design that will determine how visitors can perceive the meaning of exhibitions and works of art. Displays that are well designed will increase aesthetic value, value and can highlight the uniqueness of the work of art.